Income, egalitarianism and attitudes towards healthcare policy: a study on public attitudes in 29 countries. (January 2018) - Azar, A.; Maldonado, L.; Castillo, J.C.; Atria, J.
Abstract: Objectives: To evaluate the relationship between income and egalitarian values and attitudes towards healthcare policy. Study design: Cross-sectional and cross-national study. Methods: Data for 29 countries from the International Social Survey Programme (ISSP) 2011 were used. The dependent variables are a general attitude towards government involvement in healthcare provision and two attitudes regarding specific policies (taxes and public funding). Income and egalitarianism were also measured by using ISSP. Data were analysed using regression models that account for individual and country-level characteristics, and country-fixed effects. Results: The effect of income is small and non-significant for attitudes towards government involvement and public funding. For willingness to pay (WTP) taxes to improve healthcare services, we find a positive association with income. Results for egalitarianism suggest a positive association with government involvement in healthcare provision and significant interactions with WTP taxes. Conclusions: The distinction of dimensions and mechanisms underlying policy attitudes appears as relevant. Citizens across socioeconomic groups are motivated to support state-funded healthcare, favouring the design of non-selfish policies. These findings suggest that there is space for policymakers who seek to increase healthcare spending encouraging either policies for specific groups or broader institutional changes. Highlights: There is no income-effect on attitudes towards government involvement. Social classes' interests do not fuel disagreement about health coverage. The association between income and attitude towards healthcare public funding is unimportant. Income is positively associated with people's willingness to pay taxes to improve the system. Egalitarianism is positively associated with preferences for government involvement. Egalitarianism may be more important for rich than for the poor in explaining willingness to pay taxes.